2013
DOI: 10.1371/journal.pone.0070019
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Report from the Phase II Lamotrigine Trial in Secondary Progressive MS – Neurofilament as a Surrogate of Disease Progression

Abstract: ObjectiveLamotrigine trial in SPMS was a randomised control trial to assess whether partial blockade of sodium channels has a neuroprotective effect. The current study was an additional study to investigate the value of neurofilament (NfH) and other biomarkers in predicting prognosis and/or response to treatment.MethodsSPMS patients who attended the NHNN or the Royal Free Hospital, UK, eligible for inclusion were invited to participate in the biomarker study. Primary outcome was whether lamotrigine would signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 21 publications
3
57
1
Order By: Relevance
“…A previous study in secondary progressive MS reported serum NfH levels to correlate with brain atrophy and clinical measures such as EDSS and MSFC. 4 Future studies will show if these discrepancies relate to differences in disease stage or analytical performance of bioassays with higher sensitivity like ECL or single molecule analysis technologies vs conventional ELISA. 8 Analyses of changes in brain volume require considerable follow-up and are affected by different factors not directly related to axonal loss such as fluid shifts, aging, remyelination, and astrogliosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in secondary progressive MS reported serum NfH levels to correlate with brain atrophy and clinical measures such as EDSS and MSFC. 4 Future studies will show if these discrepancies relate to differences in disease stage or analytical performance of bioassays with higher sensitivity like ECL or single molecule analysis technologies vs conventional ELISA. 8 Analyses of changes in brain volume require considerable follow-up and are affected by different factors not directly related to axonal loss such as fluid shifts, aging, remyelination, and astrogliosis.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoassays for both NfL and NfH have been extensively published and have short-term and long-term prognostic value in various neurologic disorders. [2][3][4][5] The phase II riluzole trial in participants with early multiple sclerosis (MS) was a randomized, double-blind, placebo-controlled study assessing the putative neuroprotective effect of riluzole. The primary outcome of the trial, brain atrophy, was negative.…”
mentioning
confidence: 99%
“…In addition, serum NF-H levels were shown to decrease during SPMS, when patients were treated with Na + channel blocker, lamotrigine (based on serum lamotrigine adherence) [67]. The serum levels of NF-H were shown to correlate with clinical disability, EDSS and MRI cerebral atrophy [67] which further supports the notion that serum NF-H levels can manifest during disease progression and more likely in chronic MS (Figure 1).…”
Section: Molecular Biomarkers: We Are Not There Yetmentioning
confidence: 62%
“…Sodium channel inhibitors can exhibit marked neuroprotective effects in induced-relapsing EAE through effects on nerves and microglia (Waxman 2002;Al-Izki et al 2014;Morsali et al 2013). Sodium channel blockers used to treat epilepsy may also have some neuroprotective potential in MS (Gnanapavan et al 2013). This is perhaps consistent with the mechanism of action of CBD, although clinically CBD does not appear to have the side-effect potential of some clinical sodium channel blockers, which limited drug compliance and the perceived success of clinical trials of this compound class in MS (Kapoor et al 2010;Gnanapavan et al 2013).…”
Section: Lack Of Marked Immunosuppressive Effects Of Cannabinoids In Eaementioning
confidence: 99%